Serum phosphate level and the outcome of coronary artery disease after coronary revascularization. (25th November 2020) - Tsai, T.Y; Lim, S.S; Yang, Y.L; Chan, S.C; Hsu, P.F; Wu, C.H; Huang, S.S; Lin, S.J; Pan, J.P; Lu, T.M; Huang, P.H; Leu, H.B
Abstract: Background: Elevated serum phosphate levels have been linked with increased risk of cardiovascular disease and mortality with conflicting results. However, whether phosphate level is associated with poor outcome for CAD patients after successful percutaneous coronary intervention (PCI) remained undetermined. Purpose: We aimed to investigate the relationship between phosphate levels and the outcome of CAD patient undergoing PCI. Methods: We enrolled 2894 patients (2220 male 71.59±12.20 y/o) with coronary artery disease (CAD), who received successful coronary intervention, in a cohort from our hospital from 2006 to 2015. The baseline characteristics, biochemical data and procedure details were collected. Serum phosphorus levels were analyzed to correlate with long-term outcome. The primary outcome was the composite of cardiac death, nonfatal MI, nonfatal stroke (MACE). The secondary event was MACE and hospitalization for heart failure. Results: During an average 65.06±32.1-month follow-up, there were 173 cardiovascular deaths, 211 nonfatal myocardial infarctions, 91 nonfatal strokes, 416 hospitalizations for heart failure, and 579 revascularization procedures. There was a J-curve like linear association between serum phosphorus and future adverse event. In the multivariate analysis adjusted with comorbidities including underlying renal function, subjects with increasing every 1 mg/dL in serum phosphorus level had a higher risk of MACE (HR: 1.13, 95% CI: 1.03–1.24), cardiovascular death (HR: 1.37, 95% CI: 1.22–1.55), heart failure-related hospitalization (HR: 1.12, 95% CI: 1.02–1.23), and total major CV events (HR: 1.12, 95% CI: 1.05–1.21). (Figure) Conclusion: Serum phosphate level is significantly associated with increased risk of adverse events in CAD patients after successful PCI even considering underlying renal function. Funding Acknowledgement: Type of funding source: None